Samoocena młodzieży z niepełnosprawnością wzroku w zakresie „ja perspektywicznego” - Niemiec, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
A young person's perception of his past, present, and future life is shaped during his adolescence. The potential/prospective self of an adolescent includes his ideas and plans concerning his future life and, therefore, constitutes an important source of his motives for activity and development. This paper presents results of its author's own research on the ways in which adolescents with visual disability receiving special education in the Silesian Voivodship perceive their own future lives. The theoretical part of the paper contains an analysis of the concept of self-perception and related concepts. Special attention is paid to defining different kinds of self-perception, analyzing their functions, and indicating factors that determine their development during adolescence. An overview of selected pieces of research on the self-image of the blind and visually impaired people allowed a description of the influence of self-perception on social and personal functioning of adolescents with visual disability.